2003
DOI: 10.1590/s0004-282x2003000600014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetyl-L-carnitine on Vip-ergic neurons in jejunum submucous plexus of diabetic rats

Abstract: -The effect of the treatment with acetyl-L-carnitine (ALC) on neurons releasing the vasoactive intestinal polypeptide (VIP) of the submucous plexus in the jejunum of diabetic rats was the purpose of our investigation. Diabetes (DM) was induced by injecting streptozotocin endovenously (35mg/kg). After sacrificing the animals, the jejunum was collected and processed for VIP detection. Four groups were used: C (nondiabetic), CC (non-diabetic treated with ALC), D (diabetic), DC (diabetes treated with ALC). We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(23 reference statements)
2
9
0
1
Order By: Relevance
“…Thus, we can infer that diabetes promoted a reduction of neuron metabolism, leading to the death of a portion of its neuronal population. We observed a reduction of more than half of these neurons, and diabetic neuropathy was observed, similar to studies that used other experimental models of diabetes and evaluated different regions of the gastrointestinal tract, including the stomach (Takahashi et al 1997;Fregonesi et al 2001), duodenum (Pereira et al 2006;Zanoni et al 2011;Lopes et al 2012), jejunum (Defani et al 2003;De Freitas et al 2008;Alves et al 2010;HermesUliana et al 2014), ileum Shotton and Lincoln 2006;Pereira et al 2011), cecum (Zanoni et al 1997;Zanoni et al 2011), and proximal colon (Tashima et al 2007;Roldi et al 2009). The development of neuropathy affects different types of enteric neurons, which are responsible for the control of important functions, such as motility, secretion, blood flow, and growth aspects of the local mucosal immune system (Furness 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, we can infer that diabetes promoted a reduction of neuron metabolism, leading to the death of a portion of its neuronal population. We observed a reduction of more than half of these neurons, and diabetic neuropathy was observed, similar to studies that used other experimental models of diabetes and evaluated different regions of the gastrointestinal tract, including the stomach (Takahashi et al 1997;Fregonesi et al 2001), duodenum (Pereira et al 2006;Zanoni et al 2011;Lopes et al 2012), jejunum (Defani et al 2003;De Freitas et al 2008;Alves et al 2010;HermesUliana et al 2014), ileum Shotton and Lincoln 2006;Pereira et al 2011), cecum (Zanoni et al 1997;Zanoni et al 2011), and proximal colon (Tashima et al 2007;Roldi et al 2009). The development of neuropathy affects different types of enteric neurons, which are responsible for the control of important functions, such as motility, secretion, blood flow, and growth aspects of the local mucosal immune system (Furness 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Among the chronic complications caused by diabetes, neurological manifestations are the most common, affecting both the autonomic and peripheral nervous systems and impairing the quality of life of patients (Chandrasekharan et al 2011). Our research group found that diabetes mellitus reduced the density of myenteric neurons and enteric neural plasticity in various segments of the digestive system (Takahashi et al 1997;Zanoni et al 1997;Fregonesi et al 2001;Defani et al 2003;Zanoni et al 2003;Pereira et al 2006;Tashima et al 2007;Zanoni et al 2007;De Freitas et al 2008;Roldi et al 2009;Alves et al 2010;Pereira et al 2011;Zanoni et al 2011;Lopes et al 2012;Hermes-Uliana et al 2014). These changes in enteric innervation that arise from diabetes are attributable to persistent hyperglycemia that produces numerous metabolic changes.…”
Section: Introductionmentioning
confidence: 77%
“…51 Particularly in VIP-IR neurons of the submucosal plexus of chronically diabetic animals, such alterations are represented by the increased fluorescence and cell body area. 10,31,38 From our observations and the literature data, several hypotheses have been put forward in an attempt to clarify the possible causes contributing to the increase in the cell body area, such as:…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The myenteric neurons of rats, soon after the induction of diabetes, show reduced neuronal activity, chromatolysis and degenerative alterations. 6 In chronic diabetes mellitus, alterations are seen in neuronal density and cell body area in several segments, such as the stomach, 7,8 duodenum, 9 jejunum, 10 ileum, [11][12][13] cecum 14 and colon. [15][16][17] Enteric neuronal subpopulations such as those expressing noradrenaline, acetylcholine, serotonine, 18 nitric oxide, 19 and vasoactive intestinal peptide (VIP), 20 respond differently to diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, Defani et al (2003), Fregonesi et al (2005) e Soares et al (2006) descreveram a diminuição da massa corporal em animais diabéticos tratados com glutamato monosódico, e Hernandes et al (2000) observaram diminuição significante do peso corpóreo dos animais tratados com cloreto de benzalcônio.…”
Section: Tecido Conjuntivo Associado Ao Plexo Mioentéricounclassified